Excesso de peso, obesidade abdominal e fatores associados em adultos vivendo com HIV/aids - Castro, Aline de Cássia Oliveira (2012)
OBJECTIVE: To investigate the prevalence of overweight, abdominal obesity and factors associated with these conditions in people living with HIV / AIDS (PLHA). METHODS: Cross-sectional study, developed with 270 PLHA, added 19 years or older recruited from October 2009 to January 2011 in a hospital school in Goiania. To survey the demographic, clinical and lifestyle standardized questionnaires were used. To assess food consumption it was used risk and protection for cardiovascular disease. It was collected measures of weight, height and waist circumference (WC). Body Mass Index (BMI) ≥ 25 kg/m2 was considered to classify overweight and WC ≥ 102 for men and ≥ 88 for woman for abdominal obesity. It was used chi-square test or Fisher exact test to assess the associations. We also calculated as a measure of effect the prevalence ratio (PR), using Poisson regression simple, with a confidence interval of 95% (CI95%). We used Poisson regression with multiple hierarchical analyses for both outcomes. The project was approved by the Ethics Committee of the Hospital of the Federal University of Goiás. RESULTS: The prevalence of overweight was of 33.7% (CI95% 28.2-39.7) and abdominal obesity of 12.6% (95% CI 9.0-17.3). It was observed after multivariate analysis, for the outcome overweight, association with age of 40-49 years (PR:1,16 – CI95%1,05-1,28) and ≥ 50 years (PR: 1.20 – CI95%1,06-1,36), non-use of Highly Active Antiretroviral Therapy (HAART) (PR: 1.15 – CI95%1,05-1,25) and first tertile of risk consuption (PR: 1.15– CI95%1,04-1,28). For the outcome abdominal obesity it was observed association with: female gender (PR: 4.91– CI95%2,49-9,70), age 40-49 years (PR: 4.88 – CI95%1,99-11,98) and ≥ 50 years (PR: 4.99 – CI95%1,87-13,29), personal income greater than four minimum wages (PR: 2.87 – CI95%1,35-6,11) and count CD4 +> 350 cells / mm ³ (PR: 2.45 – CI95% 1,13-5,35). CONCLUSIONS: It was high prevalence of overweight and abdominal obesity, especially amond females, persons older than 40 years without antiretroviral therapy in the lowest tertile of risk foof consumptio, with higher income and T lymphocyte count CD4+. The data in this study point to the need for further monitoring of the nutritional status of this population and development strategies and practices that produce desirable results to the prevention and control of these conditions.